Faktor-Faktor Yang Berhubungan Dengan Kejadian Hipertensi Pada Laki-Laki Usia Dewasa Muda Di Wilayah Kerja Puskesmas Bulu Kabupaten Sukoharjo - Nur Widiansah, Herman; , Anisa Catur Wijayanti, S.KM.,M.Epid (2016)
The high rates smoking, alcohol consumption and physical activity were lower in men's young adult that may affect a person's quality of life and productivity. This can cause various disease, one of which is hypertension. The aim of this study was to analyze the factors related in hypertension of the men's young adult at the region of Puskesmas Bulu Sukoharjo district. Type of this research was observational research with case control design. The population in this study were 56 men's patient aged 20-40 years old who suffered hypertension at Puskesmas Bulu Sukoharjo district in 2015 and 2016 until June. Selection of the sample in the case group were 28 people and control group as many as 42 people. The sampling technique in this study was total sampling for the case and control groups while taken from the nearest neighbor of group home case. Statistical test technique used chi square test and Fisher's Exact Test. The results showed that there was no relation between physical activity (p= 0.215), smoking activity (p= 1.0), and alcohol consumption with hypertension (p = 0.516) in Puskesmas Bulu Sukoharjo district.